Identification and gene expression analysis of cytosine-5 DNA methyltransferase and demethylase genes in Amaranthus cruentus L. under heavy metal stress - Lancíková, Veronika; Kačírová, Jana; Hricová, Andrea (Frontiers in Plant Science, 2023)
Amaranth has become increasingly popular due to its highly nutritious grains and ability to tolerate environmental stress. The mechanism underlying defense and adaptation to environmental stress is a complicated process involving DNA methylation and demethylation. These epigenetic features have been well documented to play an important role in plant stress response, including heavy metal-induced stress. This study was aimed at the identification and analysis of cytosine-5 DNA methyltransferase (C5-MTase) and demethylase (DMTase) genes in Amaranthus cruentus. Eight C5-MTase and two DMTase genes were identified and described in response to individual heavy metals (Cd, Pb, Zn, Mn) and their combination (Cd/Pb, Cd/Zn, Pb/Zn) in root and leaf tissues. Studied heavy metals, individually and in combinations, differentially regulated C5-MTase and DMTase gene expression. Interestingly, most of the genes were transcriptionally altered under Zn exposure. Our results suggest that identified amaranth MTase and DMTase genes are involved in heavy metal stress responses through regulating DNA methylation and demethylation level in amaranth plants.